Dignitas Voluntas - Vita - Überlegungen zur Sterbehilfe aus rechtshistorischer, interdisziplinärer und rechtsvergleichender Sicht Göttinger Antrittsvorlesung im Januar 2006 - Schumann, Eva (Universitätsverlag Göttingen, 2006)
Contrary to the common constriction of the euthanasia-discussion on "self-determination at the end of life" Eva Schumann claims rethinking in dealing with seriously ill and dying people. To meet their needs in her view a comprehensive access to outpatient and inpatient palliative care facilities is recquired and also improvements of care in nursing homes as well as offers to improve the integration of members into care. These claims conclude the discussion between assistance in dying (indirect euthanasia), and assistance to die (active and passive euthanasia). Taking account historical, interdisciplinary and comparative law issues it is demonstrated that the formal legal distinction between the various case groups of euthanasia not sufficiently takes into account the social dimension of dying.